열수 침지 처리가 치콘 절단면의 적변 억제에 미치는 영향 - 정현진(Hyun Jin Jung); 강호민(Ho-Min Kang) (Weon'ye gwahag gi'sulji, 2014)
Hot water dipping test was conducted for chicon to restrict red discoloration of its basal part which impairs the product value during sales. Hot water dipping treatment was given to chicon for 4 min and for 8 min at $38^{°}C$ and for 2 min and 4 min at $42^{°}C$, and for 1 min and 2 min at $45^{°}C$, along with control (for one min at $20^{°}C$). The red discoloration indices of basal part of chicon during sensory evaluation on the sixth day of storage under the storage temperature at $10^{°}C$ was lower at $42^{°}C$ for 2 min, $42^{°}C$ for 4 min and $45^{°}C$ for 1 min treatments. The color change value of the basal part in chicon measured by colorimeter showed that the lowest ${Δ}a^*$ and ${Δ}h$ were maintained in the basal part of chicon treated at $42^{°}C$ for 2 min. Whereas, color changes in $42^{°}C$ for 2 min and $45^{°}C$ for 1 min treatments were significantly low as compared with that of control. The contents of total phenolic compounds which are the substances that cause red discoloration of basal part in chicon were lowest at $42^{°}C$ for 2 min, $42^{°}C$ for 4 min and $45^{°}C$ for 1 min treatments. The activity of phenylalanine ammonia lyase (PAL) resposible for in the synthesis of phenolic substances was the least in $42^{°}C$ for 2 min treatment. Whereas, PAL activity of the chicons treated a t $42^{°}C$ for 2 min and at $45^{°}C$ for 1 min were significantly lower than that of control. However, red discoloration was progressed as similar level with that of control in the basal part of chicon at $45^{°}C$ for 2 min. The contents of total phenolic compounds and PAL activity in this treatment were not significantly different from those in control. The polyphenol oxidase (PPO) activity which causes red discoloration of cut tissues was low in all the treatments including $42^{°}C$ and $45^{°}C$ treatment at which no inhibition effects of the red discoloration of basal part of chicon were observed. When the correlation coefficient between each investigated index was tested, most of them showed high correlation except the PPO activity and particularly and the red discoloration index and sensory evaluation ${Δ}h$ values, and PAL activity and total phenolic compounds content were $r=0.927^{**}$, and $r=0.942^{**}$, respectively. 치콘의 판매 중 상품성 저하의 원인이 되는 치콘 절단면적변 현상을 억제하기 위해 열수 침지 실험을 실시하였다. 열수침지처리로는 대조구($20^{°}C$ 1분)과 $38^{°}C$에서의 4분, 8분, $42^{°}C$에서의 2분, 4분, 그리고 $45^{°}C$에서의 1분, 2분을 두었다. 색차계로 측정한 ${Δ}a^*$과 ${Δ}h$값은 $42^{°}C$ 2분 처리에서는 가장 낮게 유지되었으며, $42^{°}C$의 2분과 $45^{°}C$의 1분 처리구에서는 대조구보다 유의 있는 낮은 값을 나타내었다. $10^{°}C$에 저장 6일째 관능 평가한 절단면의 적변지수는 $42^{°}C$의 2분과 4분 처리 그리고 $45^{°}C$의 1분 처리에서 낮았다. 적변의 원인 물질이 되는 총페놀함량을 저장 6일째 조사하였는데, 이 또한 절단면의 색변화가 적었던 $42^{°}C$의 2분과 4분 처리 그리고 $45^{°}C$의 1분 처리에서 낮았다. 페놀물질 합성에 관여하는 PAL 활성은 $42^{°}C$ 2분 처리에서는 가장 낮은 값을 보였으며, $42^{°}C$의 2분와 $45^{°}C$의 1분 처리구에서는 대조구보다 유의 있는 낮은 수치를 보였다. 그러나 가장 강한 열처리였던 $45^{°}C$의 2분 처리에서는 절단면의 적변이 대조구와 유사한 수준으로 진행되었으며, 페놀함량과 PAL 활성도 대조구와 차이가 없었다. 공기에 노출된 절단조직에서 페놀물질을 산화시켜 적변을 일으키는 PPO의 활성은 $42^{°}C$와 $45^{°}C$의 모든 처리구에서 낮았는데, 특히 다른 조사항목에서는 모두 대조구와 유사한 수준을 보였던 $45^{°}C$의 2분 처리구가 가장 낮은 수치를 보였다. 또한 각 조사항목간 상관관계에서, PPO를 제외한 모든 조사항목간에서는 대부분 고도의 상관관계를 보였으며, 특히 관능평가한 적변지수와 ${Δ}h$값은 $r=0.927^{***}$를, PAL 활성과 총 페놀물질 함량과는 $r=0.942^{***}$의 고도의 상관관계를 보였다.